The impact of Key Audit Matters (KAMs) on financial information quality: Evidence from Lebanon - Joelle Matta; Khalil Feghali (Indonesian Management and Accounting Research, 2020)
The purpose of this study is to discover the impact of Key Audit Matters (KAMs) on financial information quality and their value for Lebanese auditors. The value creation of KAMs is determined by its financial information quality, its ability to help during investment decision and its effect on the audit expectation gap. The research is conducted through a survey that was filled by external auditors who audit Lebanese banks exclusively, and are involved in the new audit report. The main results show that reporting by using Key Audit Matters adds value to the audit report from the perspective of Lebanese external auditors, and can reduce information asymmetry, increase trust in accounting and reduce the expectation gap. Moreover, the results marked that KAM improves the auditee's understanding in the audited entity, builds confidence in the audited financial statements, and helps to reduce the audit expectations gap.